Is the bonding of self-adhesive cement sensitive to root region and curing mode? - BOING, Thaynara Faelly; GOMES, Giovana Mongruel; GOMES, João Carlos; REIS, Alessandra; GOMES, Osnara Maria Mongruel (Journal of Applied Oral Science, 2017)
Objectives To evaluate the influence of two curing techniques on the degree of conversion (DC) of resin cements and on bond strength (BS) of fiber posts in different regions of root dentin. Material and Methods Twenty single-rooted premolars were endodontically treated, and the post spaces were prepared. The roots were randomly divided into two groups (n=10), according to the activation mode of the resin cement RelyX™ U200 (3M ESPE Saint Paul, MN, USA): conventional (continuous activation mode) and soft-start activation mode (Ramp). The posts (WhitePost DC/FGM) were cemented according to the manufacturer’s recommendations and, after one week, the roots were cross-sectioned into six discs each of 1-mm thickness, and the cervical, medium, and apical thirds of the root canals were identified. The DC was evaluated under micro-Raman spectroscopy and the BS was evaluated by the push-out test. The data were analyzed by two-way ANOVA and Tukey’s test (α=0.05). Results Neither the activation mode nor the root regions affected the DC of the resin cement. Higher BS was achieved in the soft-start group (p=0.036); lower BS was observed in the apical third compared to the other root regions (p